Hepatic protein tyrosine phosphatase receptor gamma links obesity-induced inflammation to insulin resistance. Issue 1 (December 2017) - Brenachot, Xavier; Ramadori, Giorgio; Ioris, Rafael; Veyrat-Durebex, Christelle; Altirriba, Jordi; Aras, Ebru; Ljubicic, Sanda; Kohno, Daisuke; Fabbiano, Salvatore; Clement, Sophie; Goossens, Nicolas; Trajkovski, Mirko; et al.
Abstract Obesity-induced inflammation engenders insulin resistance and type 2 diabetes mellitus (T2DM) but the inflammatory effectors linking obesity to insulin resistance are incompletely understood. Here, we show that hepatic expression of Protein Tyrosine Phosphatase Receptor Gamma (PTPR-γ) is stimulated by inflammation in obese/T2DM mice and positively correlates with indices of inflammation and insulin resistance in humans. NF-κB binds to the promoter of Ptprg and is required for inflammation-induced PTPR-γ expression. PTPR-γ loss-of-function lowers glycemia and insulinemia by enhancing insulin-stimulated suppression of endogenous glucose production. These phenotypes are rescued by re-expression ofPtprg only in liver of mice lackingPtprg globally. Hepatic PTPR-γ overexpression that mimics levels found in obesity is sufficient to cause severe hepatic and systemic insulin resistance. We propose hepatic PTPR-γ as a link between obesity-induced inflammation and insulin resistance and as potential target for treatment of T2DM. During obesity, chronic inflammation leads to insulin resistance and diabetes. Here, Brenachot et al. show that Protein Tyrosine Phosphatase Receptor Gamma is upregulated in obesity by inflammatory signals and correlates with insulin resistance in humans. Its deletion in mouse models of obesity and inflammation ameliorates insulin resistance by suppressing glucose production.